Materials Design for Language m-Learning - Pukšič, Dejan; Zemljak Jontes, Melita; Krašna, Marjan (Revija za elementarno izobraževanje, 2015)
Today’s smart phones are versatile multimedia devices. Their processing power is incredible compared to decades-old personal computers (PCs), and the time is right to use them in education. The touch screen has provided a haptic user interface that cannot be considered as merely another mouse. The design of m-learning materials therefore needs to follow a special set of rules to maximize the efficiency of constraints posed by the devices and the user interface. In the article the design considerations are presented in the context of a practical application for using mobile devices in language learning with the application BlaBla™.
Keywords: m-learning; design; mobile-assisted language learning (MALL); haptic user interface